Ferulic acid production from banana stem waste: kinetic study - Joanne, Tey Choo Hong (2013)
For an agriculture-intensive country like Malaysia, the abundantly-available organic wastes such as banana stem provide an opportunity for the conversion into highly-sought compounds such as ferulic acid. Ferulic acid offered variety of physiological benefits used in cosmetics, food preservation and bio-production of vanillin. In this research, the soil mixed culture was mixed with banana stem wastes in an incubator shaker followed by sample collection at every 6-hours interval for the next 60 hours. Next, HPLC (high performance liquid chromatography) analysis was performed to determine the amount of ferulic acid presence. The purpose of this study was to determine the kinetic constants (Kx, Km and Vmax) from the modified biomass and Michaelis –Menten equation by using the Runge-Kutta 4th method with the aids of Microsoft Excel Solver. The kinetic constants were reported to be Kx = 0.005/ hour, Km = 0.044 mmol/ L and Vmax = 3.66 x10 -6 μmol/ min. The yield for ferulic acid production was 14.54 mg/g. Furthermore, the R2 for biomass and substrate concentration were 0.86 and 0.89 respectively. In this research, the kinetic constants and the yield for ferulic acid production were taking precedent compared to other researches due to the banana stem waste used was high in nutrient content and easy to access by soil mixed cultures. Hence, the microbes grow well and large amount of enzyme feruloyl esterase can deliberated promptly to cleave the ester linkage joined between the cross-link of polysaccharides ends with more ferulic acid formation